Pendampingan Masyarakat Pada Perencanaan Desain Awal Pembangunan Tempat Pengolahan Sampah Guna Mengurangi Volume Sampah - Dharwati P. Sari; ‪Pandu K. Utomo (Yayasan Kajian Riset dan Pengembangan RADISI, 2021)
Design planning as an initial design stage in a building construction are needed as a work reference for contractors and supervisors as well as a description of the work to be carried out of transparency for the owner and people who affected. This initial design is between the preliminary study and design budget stage. Nowadays waste management are needed not only in urban areas but also in rural areas for better garbage management. The purpose of this community service is to integrate existing the knowledge on campus to be applied in society. The method used is assistance in planning the initial design of the waste processing site. The results of this community service activity are the 3-dimensional building, front view and side view which is used as a refence in calculating the budget plan and development work. The community participates by having discussions regarding the of the design waste processing site so that it can match with the requirements of the community and ease of construction later.